ENT 530 Social Media Portfolio: Dsquarescarves / Intan Nordini Mohd Amin - Mohd Amin, Intan Nordini (2020)
Dsquarescarves offers variety colors and types of scarf in order to give satisfaction of customers. Dsquarecarves were sold at a very reasonable price and our target market is younger generation in the range on 10-45 years old. Dsquarescarves marketing strategy is to emphasize the quality and pride of the product at the same time. It offers affordable price where younger generation even at the age of 10 able to buy this product. Thus, I develop marketing strategy that gives attraction to buy our scarves. The management of Dsquarescarves consists by Intan Nordini Binti Mohd Amin. I create Facebook in order to expand my business through social media and learn on how to post on Facebok whether to post teaser, soft sell or even hard sell. From this, we are also required to create e-Commerce to record the sales through the portal. It is a big challenge for me as it is an individual project and require lots of works to do